2020
DOI: 10.1111/ane.13225
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in multiple sclerosis at general hospital level

Abstract: | 491 wileyonlinelibrary.com/journal/ane | INTRODUC TI ONSeveral new disease-modifying therapies (DMTs) have emerged during the last decades for people with multiple sclerosis (MS), which brings both opportunities and challenges to daily praxis. There are multiple issues other than drug efficacy that must be addressed before deciding on treatment modality. Besides disease-related inflammatory aggressiveness and subjects' susceptibility to drug-specific adverse events, subjects' preferences, and cost-benefit as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Late onset neutropenia is a well-known side effect of rituximab treatment 18 but has only been documented in few MS-patients treated with rituximab in retrospective studies. 19,20 Our results indicate that neutropenia may be underreported if not monitored.…”
Section: Discussionmentioning
confidence: 76%
“…Late onset neutropenia is a well-known side effect of rituximab treatment 18 but has only been documented in few MS-patients treated with rituximab in retrospective studies. 19,20 Our results indicate that neutropenia may be underreported if not monitored.…”
Section: Discussionmentioning
confidence: 76%
“…An increasing body of evidence supports the high efficacy and the low drug discontinuation rate of B-cell-depleting anti-CD20-antibody RTX for the treatment of MS. Longterm observation of RTX therapy in RA and in NMOSD suggests that RTX is highly effective, safe and well tolerated [38,41,70,81,85]. Two large randomized clinical trials and results from large real-world studies have confirmed its safety and efficacy in both RRMS and PMS [31,37].…”
Section: Discussionmentioning
confidence: 96%
“…Overall, there were similar incidences of infections in the placebo (71.4%) and RTX group (69.7%) in the first phase II study in MS; however, an increased incidence of urinary tract infections and sinusitis was found in RTX arm compared to placebo [31]. In a recent retrospective observational study of 84 relapsing MS treated with RTX, 36 infections were reported (among 53 non-infusion-related adverse events), of which four were serious, including a case of pneumonia with concomitant late-onset neutropenia [85].…”
Section: Susceptibility To Infectionsmentioning
confidence: 99%
“…Particularly, Rituximab (RTX), a chimeric monoclonal antibody directed at CD20 positive B lymphocytes is considered a selective immunosuppressant used in different in clinical practice (500-1000 mg, every 3-6 months, or on demand at B cells detection of ≥2% of B cells) [7][8][9][10]17]. Recent real-world experiences have shown that patients with either NMO or MS disease benefit efficiently from RTX with favorable safety and cost-effectiveness profile [17][18][19][20]. However, It has been suggested that the risk of serious infection for patients with MS or NMOSD varies depending on the DMTs being used.…”
Section: Introductionmentioning
confidence: 99%